1994
DOI: 10.1128/aac.38.10.2357
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of disk diffusion test and its clinical significance for susceptibility testing of metronidazole against Helicobacter pylori

Abstract: Nitroimidazoles, including metronidazole and tinidazole, have been used in multiple antimicrobial therapy strategies to eradicate Helicobacterpylori in peptic ulcer patients and nonulcer dyspeptic patients (1, 19). However, emergence of primary resistance and acquired resistance to these kind of drugs in H. pyloni may lead to treatment failure (3,7,10,11,21,27). Thus, evaluation of H. pylotn susceptibility to metronidazole before treatment appears to be important. Metronidazole resistance rates from 6.4 to 84%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
2

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 20 publications
2
50
2
Order By: Relevance
“…These values are lower when an intermediate group is created, but accordance is only 75.3%. In other studies, breakpoints determined with linear regression for metronidazole were 16 and 21 mm [23], and 20 and 26 mm [24], but experimental conditions differed from those of the present study. Chaves et al [23] reported a higher correlation (r 2 = 0.88), but did not include isolates with MICs higher than 32 mg/l.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…These values are lower when an intermediate group is created, but accordance is only 75.3%. In other studies, breakpoints determined with linear regression for metronidazole were 16 and 21 mm [23], and 20 and 26 mm [24], but experimental conditions differed from those of the present study. Chaves et al [23] reported a higher correlation (r 2 = 0.88), but did not include isolates with MICs higher than 32 mg/l.…”
Section: Discussioncontrasting
confidence: 49%
“…Thus, the MICs and inhibition zone diameters of 94 isolates were plotted and breakpoints with this method were established with the following restrictions: maximum 5% of false resistant misclassified isolates and maximum 1% of false susceptible misclassifications [22]. Fulfilment of these conditions for the metronidazole data made it necessary to define an intermediate group of isolates with MICs between 4 and 8 mg/l as has been proposed by other authors [23,24]. In this study, isolates with inhibition diameters from 10 to 24 mm were classified as intermediate susceptible.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial sensitivities were determined using the disc diffusion method, with a zone of < 20 mm taken to be indicative of metronidazole resistance. 3,4 Patients were offered enrolment to the study if they were aged between 18 and 80 and were H. pylori positive, as de®ned by a positive rapid urease test. They subsequently underwent 13 C-UBT, and were included in the analysis if the 13 C-UBT was positive, and had at least one other positive result from histology, rapid urease test or antral biopsy culture.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that triple therapy consisting of a PPI, clarithromycin, and a nitroimidazole are effective at eradicating H pylori infection in patients harbouring metronidazole resistant strains13-15; others show that the efficacy is significantly decreased when metronidazole resistance is present 16-19. Several factors might have contributed to these differences, including different methods used for diagnosing metronidazole resistance,20 21 different cut off values for determining the minimum inhibitory concentrations,22 23 and probably different locations where biopsy samples were taken 24. In patients who harbour metronidazole resistant strains, the eradication rate is about 30% lower than in those infected with metronidazole sensitive strains, when treated with bismuth, metronidazole, and tetracycline or amoxicillin triple therapy 8.…”
Section: Factors Leading To Treatment Failurementioning
confidence: 99%